2013
DOI: 10.1111/hae.12291
|View full text |Cite
|
Sign up to set email alerts
|

A review of evidence about behavioural and psychological aspects of chronic joint pain among people with haemophilia

Abstract: Joint pain related to haemophilia affects large numbers of people and has a significant impact on their quality of life. This article reviews evidence about behavioural and psychological aspects of joint pain in haemophilia, and considers that evidence in the context of research on other chronic pain conditions. The aim is to inform initiatives to improve pain self-management among people with haemophilia (PWH). Reduced pain intensity predicts better physical quality of life, so better pain management should l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 109 publications
1
24
0
2
Order By: Relevance
“…This concurs with a study of adult haemophilia patients where more than 80% of the participants used factor and rest for pain relief . Administration of clotting factor concentrates is the key in management of haemophilia . However, 20.69% of the current study subjects who had pain and had to use a factor replacement product did not administer factor for pain relief.…”
Section: Discussionsupporting
confidence: 88%
“…This concurs with a study of adult haemophilia patients where more than 80% of the participants used factor and rest for pain relief . Administration of clotting factor concentrates is the key in management of haemophilia . However, 20.69% of the current study subjects who had pain and had to use a factor replacement product did not administer factor for pain relief.…”
Section: Discussionsupporting
confidence: 88%
“…However, differences in physical HRQoL (PCS) were not observed in our study, which is a surprising finding given that prophylaxis is associated with fewer joint bleeds and less pain [7], and a recent review found that joint status was associated with both social and emotional well-being [44]. One possible explanation for the findings in our study is that physical sequelae of the disease have not yet manifested in AYAs, a hypothesis also set forth by Poon et al [20].…”
Section: Discussionmentioning
confidence: 48%
“…Chronic joint pain dominates the literature on self‐management, but the acute pain of a bleed is also mentioned in most surveys. Better pain management leads to improved physical HRQoL, whereas increased pain acceptance leads to improved mental HRQoL . In studying the management of pain by PWH, it was found that they used task‐oriented coping at the same frequency as a control group, which would seem to be a better approach than using emotion‐oriented coping.…”
Section: Consensus From Recent Literaturementioning
confidence: 99%